Changing the Game: Insights from Howard-Delafield International’s Digital Innovation for Social Impact in India - Shankar, Lalita (Digital Repository of Theses - SSBM Geneva, 2024)
This doctoral thesis investigates the integration of leadership practices, organizational culture, and risk-taking in Howard-Delafield International's (HDI) development of "Go Nisha Go" (GNG), a mobile game designed to improve reproductive health education among adolescent girls in India. It uses a case study methodology to analyse HDI‘s creative and multidisciplinary product development approach, including agile leadership practices and alignment with social impact goals. The analysis revealed how HDI's leadership navigated the complexities of digital innovation within a social impact framework, successfully aligning product development with project management objectives amidst the constraints imposed by conventional models. Through qualitative exploration, the thesis explores the nuanced dynamics between leadership, organizational culture, and risk-taking that underpinned HDI's journey. The study concludes that strategic leadership stemming from a culture that embraces risk taking, agile decision making and harnessing emerging technologies for a social impact were key to the successful launch and adoption of this innovative product in India's rapidly evolving digital landscape. This research contributes to the theoretical landscape of digital innovation in social impact projects, providing a detailed blueprint for organizations aiming to leverage digital platforms for societal benefits, especially in the area of reproductive health education.